2008
DOI: 10.1007/s00464-008-9763-9
|View full text |Cite
|
Sign up to set email alerts
|

Cine-MRI detection of intraabdominal adhesions: correlation with intraoperative findings in 89 consecutive cases

Abstract: Cine-MRI provides valid preoperative information with respect to extent, location, and strength of intraabdominal adhesions. Cine-MRI is a good alternative for diagnosing abdominal adhesions because objective findings of the scan and intraoperative findings correlate very well with each other.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 30 publications
0
29
0
1
Order By: Relevance
“…As a result, other noninvasive diagnostic tools have been examined among these cine MRI [6,[20][21][22][23]. Compared with TAU, cine MRI not only enables one to visualize abdominal wall adhesions, but also adhesions between adjacent organs.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, other noninvasive diagnostic tools have been examined among these cine MRI [6,[20][21][22][23]. Compared with TAU, cine MRI not only enables one to visualize abdominal wall adhesions, but also adhesions between adjacent organs.…”
Section: Discussionmentioning
confidence: 99%
“…The most recent article was by Lang et al [32]. In their study, 89 patients with suspected adhesion-related complaints were enrolled and underwent cine MRI before surgery.…”
Section: Cine Mrimentioning
confidence: 99%
“…Radiological diagnosis of intra-abdominal adhesions is challenging. While previous reports showed that cine MRI and transabdominal ultrasonography detected adhesions to the abdominal wall fairly specifically, both carry a low sensitivity [14][15][16][17] .…”
Section: Discussionmentioning
confidence: 96%